Is a head-worn inertial sensor a valid tool to monitor swimming? - Shell, S. J.; Clark, B.; Broatch, J. R.; Slattery, K.; Halson, S. L:; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: This study aimed to independently validate a wearable inertial sensor designed to monitor training and performance metrics in swimmers.